2005
DOI: 10.1074/jbc.m410061200
|View full text |Cite
|
Sign up to set email alerts
|

FRAT-2 Preferentially Increases Glycogen Synthase Kinase 3β-mediated Phosphorylation of Primed Sites, Which Results in Enhanced Tau Phosphorylation

Abstract: Tau is a microtubule-associated protein found primarily in neurons, and its function is regulated by sitespecific phosphorylation. Although it is well established that tau is phosphorylated at both primed and unprimed epitopes by glycogen synthase kinase 3␤ (GSK3␤), how specific proteins that interact with GSK3␤ regulate tau phosphorylation has not been thoroughly examined. Members of the FRAT (frequently rearranged in advanced T-cell lymphoma) protein family have been shown to interact with GSK3␤, and FRAT-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Ser 188 conforms to consensus motifs for phosphorylation by GSK-3, PKA, and PKC, and all of these kinases phosphorylated Ser 188 in vitro. Recently, both FRAT1 and FRAT2 were shown to be phosphorylated in cells (23), and GSK-3 was found to phosphorylate FRAT2 in vitro (32). Our results indicate that GSK-3 phospho-FIGURE 9.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Ser 188 conforms to consensus motifs for phosphorylation by GSK-3, PKA, and PKC, and all of these kinases phosphorylated Ser 188 in vitro. Recently, both FRAT1 and FRAT2 were shown to be phosphorylated in cells (23), and GSK-3 was found to phosphorylate FRAT2 in vitro (32). Our results indicate that GSK-3 phospho-FIGURE 9.…”
Section: Discussionsupporting
confidence: 56%
“…2, both PKA and PKC phosphorylated wild type Myc-FRAT1. In contrast, no 32 P incorporation into the S188A 188 with human and mouse orthologs and paralogs. Conserved residues are shown in boldface type.…”
Section: Sermentioning
confidence: 94%
“…After washing IgG beads containing the immunomobilized GSK3␤ four times with phosphate-buffered saline containing 350 mM NaCl (high salt) and 0.5% Nonidet P-40, the beads were washed two additional times with GSK3 kinase buffer (20 mM Tris-Cl, pH 7.5, 5 mM MgCl 2 , and 1 mM dithiothreitol). GSK3␤ activity assays were performed as described using phosphoglycogen synthase peptide 2 or recombinant tau as substrates (37) with the exception that GSK3␤ activity was normalized to GSK␤ levels in the sample, and the data were expressed as percentages of control (GFP alone). The same immunoprecipitation was performed to detect phospho-Ser 9 GSK3␤ (Cell Signaling) in each condition.…”
Section: Methodsmentioning
confidence: 99%
“…have provided evidence that GSK3-binding proteins, such as FRAT-1 and FRAT-2, which are the proteins involved in the Wnt canonical pathway, affect GSK3␤-mediated tau phosphorylation (23,37,39). Since LRP6 is a GSK3-binding protein that attenuates its activity in in vitro assays, we next examined the effects of LRP6 on GSK3-mediated FIGURE 5.…”
Section: The C Terminus Of Lrp6 Inhibits Gsk3␤-mediated Phosphorylatimentioning
confidence: 99%
“…11 Moreover, in contrast to reports that FRAT1 prevents phosphorylation of Tau by GSK3, 29,53 it was recently observed that FRAT2 might in fact promote the GSK3-dependent phosphorylation of primed sites on Tau. 54 Thus, although it remains an attractive hypothesis that Frat allows the discrimination of primed and unprimed GSK3 substrates, this should be further investigated now that the regulation of β-catenin is understood in more detail.…”
Section: Towards Specific Inhibitionmentioning
confidence: 99%